A novel system exploits bone debris for implant osseointegration. Issue 5 (10th September 2020) - Coyac, Benjamin R.; Salvi, Giuseppe; Leahy, Brian; Li, Zhijun; Salmon, Benjamin; Hoffmann, Waldemar; Helms, Jill A.
Abstract: Background: Bone debris generated during site preparation is generally evacuated with irrigation; here, we evaluated whether retention of this autologous material improved the rate of peri‐implant bone formation. Methods: In 25 rats, a miniature implant system composed of an osseo‐shaping tool and a tri‐oval‐shaped implant was compared against a conventional drill and round implant system. A split‐mouth design was used, and fresh extraction sockets served as implant sites. Histology/histomorphometry, immunohistochemistry, and microcomputed tomography (μCT) imaging were performed immediately after implant placement, and on post‐surgery days 3, 7, 14, and 28. Results: Compared with a conventional drill design, the osseo‐shaping tool produced a textured osteotomy surface and viable bone debris that was retained in the peri‐implant environment. Proliferating osteoprogenitor cells, identified by PCNA and Runx2 expression, contributed to faster peri‐implant bone formation. Although all implants osseointegrated, sites prepared with the osseo‐shaping tool showed evidence of new peri‐implant bone sooner than controls. Conclusion: Bone debris produced by an osseo‐shaping tool directly contributed to faster peri‐implant bone formation and implant osseointegration.